SISTEM PEMBELAJARAN BAHASA ASING DI PONDOK PESANTREN NUR EL HAQ KOMBA KABUPATEN LUWU - Baharuddin, Ilham; Kartini, Kartini; Jufriadi, Jufriadi (Institut Agama Islam Negeri (IAIN) Palopo, 2023)
This study aims to understand learning management at Islamic Boarding School Nur El Haq Komba, especially in the Arabic and English learning management from planning, implementing, to evaluating learning. Another goal is to understand the obstacles encountered in the learning process at the Islamic Boarding School and how to solve the obstacles. Based on the type of data, this research is qualitative type. Data collection techniques used are documentation, observation and interviews. Data analysis techniques used are data reduction, data presentation, and verification. The data sources used are primary data and secondary data. The results of the study show that learning management at the Nur El Haq Komba Islamic Boarding School in general has adopted a khalaf (modern) learning system. In learning foreign language, the manager gives the same portion to the use of Arabic and English, but in the portion of the learning hours, learning Arabic is more than learning English. The learning obstacles that usually occur include the tight schedule of learning while in the dormitory, the infrastructure that still needs to be improved, and the mastery of the teachers in teaching still needs to be developed. Boarding school manager has also carried out several treatments in solving these obstacles.Â Kata Kunci,: Sistem Pembelajaran, Pembelajaran Bahasa Asing, Pondok Pesantren, Kabupaten Luwu